Effect of time-temperature treatments on the antioxidant activity of blue ternatea (Clitoria ternatea). - Palacio, Niambee Ruth A.
Clitoria ternatea, locally called blue ternatea or ternatea has been claimed for its health value and is commonly used in juice and salad preparations. This study intended to use dried ternatea flower for herbal tea infusion. Three time-temperature treatments (DBT) were tested in drying the blue ternatea flower to a moisture content of 5%, such as: DBT 1- 1 hr and 15 min. at 700C; DBT 2- 30 min. at 1000C; and DBT 3- 18 min at 1300C. The levels of anthocyanin of the dried flowers of DBT 1, DBT 2 and DBT3 were 121.9 mg L-1, 177.4 mg L-1 and 166.1 mg L-1, respectively. And the Radical Scavenging Activity (RSA) of the 3 treatments were 93.44%, 87.35% and 96.21% respectively. No significant differences (P>0.05) in the anthocyanin content and RSA among the 3 treatments were found probably due to the stable polyacylated anthocyanin structures in the dried flowers. The anthocyanin content and RSA of the dried flowers. The anthocyanin content and RSA of the dried flowers were compared to that of the fresh ternatea flower reported by Septimo (2015, unpublished), and were found lower by 50 mgL-1. and 50%, respectively. The anthocyanin content and RSA of the 3 treatments were poorly correlated. DBT3 was the most preferred formulation (MPF) among the three treatments. The physico-chemical values of the DBT3 were: total sugar content= 15.36 mg ml-1; aw= 0.563; pH= 6.52; %TA= 5.23x10-3; and ash content= 5.65%. No significant differences were observed among the three treatments. General acceptability of the tea infusions of the three treatments showed DBT 1 and 3 as "like slightly" while DBT 2 was rated between "like moderately" and like slightly". Time-temperature of drying did not affect the sensorial qualities of the tea because difference in flavor and aroma were indistinguishable.